Editorial [Hot Topic: Nongenomic Effects of Thyroid Hormones in Central Nervous System and Skeletal Muscle (Guest Editor: Sandra Incerpi)] - Incerpi, Sandra (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
This Theme Issue entitled ‘Nongenomic effects of thyroid hormones in Central Nervous System and Skeletal Muscle: from zebrafish to man’, is focused on the effects of thyroid hormones that are not mediated by the classical nuclear receptor, but by other receptors located on the plasma membrane or in the cytoplasm, including integrin αvβ3 and the nuclear receptor β. The first contribution is from Paul J. Davis and his group with a paper on the acute modulation of neuronal excitability by thyroid hormones, particularly the sodium current (INa). The results show that T4 inhibits neuronal excitability in a large population of Pre-Frontal Cortex (PFC) pyramidal neurons of young adult rats. T4 at nanomolar concentrations inhibits excitability in rat brain slices with their neuronal circuit intact, as shown by Vm depolarization, spike number decrease, or both in the majority of the recorded neurons. The paper of Yonkers and Ribera shows that in zebrafish embryos thyroxine, T4, but not T3, rapidly upregulates the current amplitude of a specific sodium channel subtype, Nav1.6a. In mammals, the orthologous channel, Nav1.6, is expressed at the nodes of Ranvier. The regulation of Nav1.6a channels involves a plasma membrane receptor, integrin αvβ3, indicative of a nongenomic mechanism. The binding of T4 to this integrin is inhibited by the RGD (Arg-Gly-Asp) peptide, an important functional site recognized by several different integrins. Taken together, these studies show that genomic and nongenomic actions of thyroid hormones may work in concert to regulate the density and the activity of Na+ channels in neurons. The action of T3 is predominantly genomic in the regulation of the expression of Na+ channels in excitable cells, while T4 acts nongenomically to regulate the basal activity of Na+ channels. The modulation of ion channels by thyroid hormones mediated by αvβ3 integrin, G protein, or other receptor/transducer represents a metabotropic-type signal with the involvement of second messengers and/or phosphorylation-dephosphorylation mechanisms, whereas the interaction of thyroid hormones could also be a direct one, as observed with benzodiazepine or neurosteroids for the GABA receptors, and as it appears to be in another paper of this Theme Issue (Puia). The advantage of a direct modulation could be a faster neurotransmission, but this does not seem to be the case from the paper of Yonkers and Ribera, whereas a direct effect could be responsible for the fast modulation observed by Davis and coworkers. The contribution of Puia can be considered complementary, as far as mechanism is concerned, to both Yonkers and Ribera on one side and to that of Davis et al. on the other, since it focuses on fast neurotransmission mediated by glutamate (excitatory) and Gaba (inhibitory in adult, but excitatory during development) ionotropic receptors. The author shows for both types of channels a fast modulation by thyroid hormones with a decrease in both current and frequency of synaptic potentials. These fast nongenomic effects do not depend on kinase modulation or on the involvement of the αvβ3 integrin receptor. This could again be a direct effect: the only one really compatible with very fast neurotransmission that could be highly conserved and important. This direct effect was previously hypothesized by J.V. Martin in 1996 for recombinant GABA ionotropic receptor subunits expressed in synaptoneurosomes. Of course, we need to take into account that the differences in mechanism may depend on the complexity of the model under study, zebrafish vs rat, the brain area and the experimental conditions.....